Stability and Characteristics of Red Palm Oil Nanoemulsions at Different Surfactant Ratios - Yuli Perwita Sari; Sri Dewi Oktafia; Siti Tamaroh; Toto Nugroho Triputra Maryana (Universitas Darussalam Gontor, 2026)
β-carotene is a potent antioxidant naturally present in red palm oil (RPO) at concentrations of 500-700 ppm. Despite its significant nutritional and functional benefits, the application of β-carotene in aqueous food systems remains limited due to its hydrophobic nature and high sensitivity to heat, light, and oxygen. Therefore, the development of an effective lipid-based delivery system is required to improve its dispersibility and stability. Nanoemulsions, lipid-based carriers with nanosized droplets, have emerged as an effective approach for such applications. This study aimed to evaluate the stability and physicochemical characteristics of β-carotene nanoemulsion formulated using a red palm oil-palm oil blend and produced via a low-energy emulsification method (phase inversion). Tween 80 was used as the surfactant, and distilled water as the aqueous phase. The nanoemulsions were characterized based on turbidity, particle size distribution, polydispersity index (PDI), zeta potential, pH, viscosity, color attributes, and β-carotene retention during storage at room temperature. The results showed that the surfactant-to-oil ratio significantly influenced the physical stability of the nanoemulsions. The optimal formulation, achieved at a surfactant-to-oil ratio of 3:1, produced a nanoemulsion with an average particle size of approximately 200 nm, a low polydispersity index, and a stable zeta potential for up to four weeks. Chemical stability, as measured by β-carotene content, declined markedly after 3 weeks of storage. These findings indicate that blending red palm oil with palm oil enables the formation of physically stable nanoemulsions using a low-energy method. Nevertheless, further formulation optimization is required to enhance the chemical stability of β-carotene for prolonged storage and potential application in aqueous food systems.